2007
DOI: 10.1002/pssa.200723249
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrogen on electronic structure of fcc iron in relation to hydrogen embrittlement of austenitic steels

Abstract: The total structural energy per primitive lattice cell, density of electron states, spatial distribution of electrons and elastic modulus in fcc Fe–H solid solutions are studied using the density functional theory and Wien2k program package. It is shown that hydrogen increases the density of electron states at the Fermi level. The density of conduction electrons is increased in the vicinity of hydrogen atoms, which suggests that the latter migrate over the crystal lattice surrounded by the clouds of conduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…The presence of a single H interstitial can therefore influence the bonding of at least 40 Fe atoms (octahedral H interstitial), and at least 38 Fe atoms (tetrahedral H interstitial), overall resulting in the weakening of the Fe bond strength. The weakening of Fe—Fe bonds due to the presence of interstitial H within the Fe lattice has been shown in several similar models in the literature [45, 60, 61, 62, 63, 64, 65, 66]. When H is present at an interstitial position within the Fe lattice an electron transfer of around 0.35 e − to 0.6 e − takes place from the Fe atom to the neighbouring H atom [45, 60, 66], which is well in the range of our estimation.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…The presence of a single H interstitial can therefore influence the bonding of at least 40 Fe atoms (octahedral H interstitial), and at least 38 Fe atoms (tetrahedral H interstitial), overall resulting in the weakening of the Fe bond strength. The weakening of Fe—Fe bonds due to the presence of interstitial H within the Fe lattice has been shown in several similar models in the literature [45, 60, 61, 62, 63, 64, 65, 66]. When H is present at an interstitial position within the Fe lattice an electron transfer of around 0.35 e − to 0.6 e − takes place from the Fe atom to the neighbouring H atom [45, 60, 66], which is well in the range of our estimation.…”
Section: Resultsmentioning
confidence: 61%
“…8). H atoms diffuse through the Fe lattice during cathodic charging surrounded by clouds of conducting electrons [62].…”
Section: Resultsmentioning
confidence: 99%
“…Even for fcc metals, the concentration used in Birnbaum and Sofronis (1994) is too high. This implies that the hydrogen elastic shielding mechanism, while being viable, might not be the dominant factor in HELP phenomena, as noted by other researchers (Teus et al, 2007;Taketomi et al, 2008;Gavriljuk et al, 2010) and will be revisited in this paper.…”
Section: Previous Modeling and Simulationmentioning
confidence: 83%
“…Ab initio calculations of the electronic structure in the f.c.c. iron containing carbon, nitrogen or hydrogen, as studied in [7][8][9], have shown that carbon decreases density of electron states at the Fermi level of f.c.c. iron, whereas nitrogen and hydrogen increase it (Fig.…”
Section: Atomic Interactionsmentioning
confidence: 99%